Technologia represji politycznych NKWD w latach 1939–1941 - Баран, Володимир Кіндратович; Baran, Volodymyr K. (Instytut pamięci narodowej, 2014)
У статті аналізуються обсяг та методи роботи радянських органів державної безпеки у 1939-1941 роках. Характеризується технологія політичного пошуку як основний профіль сталінських спецслужб. На підставі документів НКВС СРСР описані категорії так званого "антирадянського елемента". Виявлено особливості роботи спецслужб, спостереження, перевірки інформації, використання провокаційних методів у боротьбі з "ворогами народу". Досліджується процедура арештів, організація розслідувань та система ув'язнення, використання методів правопорушення та працівників органів внутрішніх справ у справах допиту.

The article lays down the analysis of the scope and methods of operation of the Soviet state security bodies in 1939–1941. It describes the technology of political search as the main profile of Stalin’s special services. On the basis of documents of NKVD of the USSR the categories of the so-called “anti-Soviet element” are described. Some features of the secret service work, field surveillance, mail cover check, the use of provocative methods in the struggle with “enemies of the people” are revealed. The arrests procedure, investigations organization and the system of imprisonment functioning, the use of offence methods and in-ward agents by interrogation officers are investigated. Considerable attention is paid to the activity of the Special conference at NKVD of the USSR, which was the key organ of extra-judicial punishment of the political prisoners. The article is written based on the original actual material, first of all based on the documents of the National Archives of the Security Service of Ukraine, Branch National Archives of the Ministry of Internal Affairs of Ukraine, the Russian State Archives of Social and Political History, the Russian State Archives of the Contemporary History, the State Archives of Russian Federation.
The Technology of NKVD Political Repressions 1939–1941
Keywords: NKWD; "element antyradziecki"; aresztowania; śledztwo; więzienia; NKVD; "anti-Soviet element"; agentura; secret service; arrests; investigation; prisons